2013
DOI: 10.1109/jmems.2013.2266859
|View full text |Cite
|
Sign up to set email alerts
|

A Bistable Electrostatic Silicon Nanofin Relay for Nonvolatile Memory Application

Abstract: We present a nanoelectromechanical (NEM) relay that is capable of demonstrating two stable states without on-hold power due to the influence of van der Waals force. This is realized by leveraging a silicon nanofin (SiNF) as a relay that can switch between two lateral terminals. The smallest dimension of the SiNF is 80-nm width by 2-μm length. The SiNF is able to maintain its geometrical position even after the bias voltage is turned off. Bistable hysteresis behavior with pull-in voltage (V PI ) and reset volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Table 1 compares the performance of previously reported electrostatically actuated non-volatile relays with the presented relay. To the best of our knowledge, only Soon et al 14 have reported more than 1 or 2 reprogramming cycles to date; they demonstrated 11 cycles at 50°C with a programming voltage of 10 V and reprogramming voltages between~12 and 15 V. We achieved a programming voltage…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Table 1 compares the performance of previously reported electrostatically actuated non-volatile relays with the presented relay. To the best of our knowledge, only Soon et al 14 have reported more than 1 or 2 reprogramming cycles to date; they demonstrated 11 cycles at 50°C with a programming voltage of 10 V and reprogramming voltages between~12 and 15 V. We achieved a programming voltage…”
Section: Discussionmentioning
confidence: 72%
“…Non-volatile memory requires relays that retain the switched state when power is switched off. Electrostatically operated NEM relays reported in the literature for both volatile operation 5,9,6,7,[10][11][12] and non-volatile operation [12][13][14] have architectures including a beam anchored at one end (cantilever), both ends (bridge), the centre (see-saw) and at four corners (crab leg), with different types of hinges. When actuated, the beam moves under an electrostatic force to make contact with a stationary electrode to establish the 'on' state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3(a) shows the structure of a NEM memory switch for FPGA applications. Its operation principle referring to [7] and [8] has already been confirmed experimentally [10]. It consists of two metal line electrodes, which are called selection line 1 (L 1 ) and selection line 2 (L 2 ), respectively, and a movable cantilever beam attached to the bit line (BL), which switches between L 1 and L 2 .…”
mentioning
confidence: 99%
“…This unique mechanically controlled feature endows NEM switches with several important properties for logic computation and non-volatile memory applications, which are unavailable in traditional CMOS technology, such as near zero subthreshold swing and hysteresis switch behavior. [15][16][17][18] As long as the structural and contact materials maintain their electrical and mechanical properties, the devices will be functional as designed in a high temperature environment. However, challenges still remain for recently reported M/NEM switches.…”
mentioning
confidence: 99%